Characterization and failure analysis of plastics (ASM International, 2003)
Introduction - Materials selection and design of engineering plastics - Physical, chemical, and thermal analysis of plastics - Mechanical behavior and wear - Environmental effects - Failure analysis of plastics - Reference information.